Identification of the Critical Points For Polycyclic Aromatic Hydrocarbon Contamination along the Cocoa Processing and Storage Chain in Ghana - Kwaku Owusu, Sebastian (2014)
A Thesis Submitted to the Department of Materials Engineering, Kwame Nkrumah University of Science and Technology, in Partial Fulfillment of the Requirements for the award of Master of Science Degree in Environmental Resources Management